2016
DOI: 10.1016/j.ijsu.2016.04.051
|View full text |Cite
|
Sign up to set email alerts
|

Surgical anatomy of the pyramidal lobe in cancer patients: A Prospective Cohort in a Tertiary Centre

Abstract: PL is a well established entity which is present in over one third of patients. Efforts should be made to identify PL during surgery given its bearing on the management of thyroid carcinoma as nearly 10% of these will be site of multifocal papillary carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 14 publications
0
10
1
Order By: Relevance
“…The PL is known as an ancillary lobe of the thyroid gland, correlating with the caudal end of the embryologic thyroglossal duct. Its prevalence in literature ranges from 35.7 to 60.0% in cadaver studies and from 12.3 to 61.0% when assessed during thyroid surgery [1][2][3][4][5][6][7][8][9][10]. In the present study, we observed a prevalence of 80%, which is markedly higher than what was previously reported.…”
Section: Prevalence Of the Pyramidal Lobecontrasting
confidence: 59%
See 4 more Smart Citations
“…The PL is known as an ancillary lobe of the thyroid gland, correlating with the caudal end of the embryologic thyroglossal duct. Its prevalence in literature ranges from 35.7 to 60.0% in cadaver studies and from 12.3 to 61.0% when assessed during thyroid surgery [1][2][3][4][5][6][7][8][9][10]. In the present study, we observed a prevalence of 80%, which is markedly higher than what was previously reported.…”
Section: Prevalence Of the Pyramidal Lobecontrasting
confidence: 59%
“…-Caudal: Thyroid isthmus. [2] 58.1% (61/105) Ozgur et al [3] 60.0% (24/40) Prakash et al [4] 35.7% (25/70) Milojevic et al [5] 55.2% (32/58) Surgery-based studies Geraci et al [6] 12.3% (74/604) Zivic et al [7] 61.0% (61/100) Kim et al [8] 59.8% (79/132) Ryu et al [9] 60.0% (81/135) Irawati et al [10] 36.9% (38/103) -Cranial: Approximately 1 cm cranial of the thyroid isthmus. -Lateral: lateral border of the infrahyoidal muscles.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations